Growth performance of Ceriops decandra (Griff.) Ding Hou propagules as influenced by PGR – a conservation effort - Gomathinayagam, M.; Arunprasath, A. (Ecoprint: An International Journal of Ecology, 2016)
Vegetative propagation could be an important advantage and also envisioned to be the best alternative for planting stock production in the absence or lack of seeds. In the Pichavaram mangrove forest Ceriops decandra (Rhizophoraceae) is one of the most endangered species and IUCN also declared this species as near threatened. Propagation of Ceriops decandra, by propagule cuttings, treated with Plant growth regulators is feasible and it was possible to produce three saplings from one propagule. The effect of plant growth regulators like IBA, NAA, GA3 on optimum growth medium and period of nursery care for mangrove saplings of Ceriops decandra were studied and the results revealed that best growth performance was recorded when the cuttings were treated with GA3 alone up to 2000 ppm. Combination of NAA and IBA increased the rooting and leaf formation. Among the treatments GA3 enhanced the number of leaves and roots, Shoot and root length, fresh and dry weight of roots increased to larger extent. All the plants are transferred to field in the mangrove forest of Pichavaram, Tamilnadu, India. ECOPRINT 22: 21-28, 2015